Television Reality Shows in the Arab World - Ayish, Mohammad (2011)
As much as Western-style reality television in the Middle East has gained extensive popularity among the region's audiences, it has also provoked serious ethical questions. In addressing this emerging genre, some television channels have evolved their own reality shows that emphasize local values and traditions. Based on a survey study and a focus group discussion involving University of Sharjah (United Arab Emirates) students who were exposed to two sets of reality shows, one “globalized” and the other “localized”, it was clear that both were perceived to carry converging and diverging universal and Arab-Islamic values and norms. The findings of the study suggest that convergence between indigenous and universal media ethics supports the case for a “glocalized” media ethics the Arab world needs to sustain its emerging media industries in a global context.